Trajectories of sickness absence and disability pension days among 189,321 white-collar workers in the trade and retail industry; a 7-year longitudinal Swedish cohort study - Kristin Farrants; Kristina Alexanderson (BMC, 2022)
Abstract Objective 1) identify different trajectories of annual mean number of sickness absence (SA) and disability pension (DP) days among privately employed white-collar workers in the trade and retail industries and 2) investigate if sociodemographic and work-related characteristics were associated with trajectory membership. Methods A longitudinal population-based cohort register study of all white-collar workers in the trade and retail industry in 2012 in Sweden (N = 189,321), with SA and DP data for 2010-2016. Group-based trajectory analysis was used to identify groups of individuals who followed similar trajectories of SA/DP days. Multinomial logistic regression was used to determine associations between sociodemographic and work-related factors and trajectory membership. Results We identified four trajectories of SA/DP days. Most individuals (73%) belonged to the trajectory with 0 days during all seven years, followed by a trajectory of few days each year (24%). Very small minorities belonged to a trajectory with increasing SA/DP days (1%) or to constantly high SA/DP (2%). Men had a lower risk of belonging to any of the three trajectories with SA/DP than women (OR Low SA/DP 0.42, 95% CI 0.41-0.44; Increasing SA/DP 0.34, 0.30-0.38; High SA/DP 0.33, 0.29-0.37). Individuals in occupations with low job control had a higher risk of belonging to the trajectory High SA/DP (OR low demands/low control 1.51; 95% CI 1.25-1.83; medium demands/low control 1.47, 1.21-1.78; high demands/low control 1.35, 1.13-1.61). Conclusion Most white-collar belonged to trajectories with no or low SA/DP. Level of job control was more strongly associated with trajectory memberships than level of job demands.